Mobile Phone Usage Pattern among Secondary School Children in Some Selected Rural Schools. (Anwer Khan Modern Medical College Journal, 2023)
Background: Mobile phones are an integral part of our modern life. The use of mobile phone for various purposes (including educational) has increased in recent few years in Bangladesh. The aim of the study was to explore the mobile phone usage pattern among secondary school children in rural schools of Bangladesh.Materials and Methods: This descriptive type cross sectional study was carried among 295 secondary school children by purposive sampling technique from 1st to 31st December, 2019 in different villages of Dhamrai Upazilla, Dhaka. Data were collected by duly pretested a semi-structured questionnaire through face to face interview.Results: The study revealed that, most of the respondents were in class X (36.61%) with female predominance (56.94%). Among them,63.72% were from nuclear family & majority 56.61% of the respondents had family monthly income BDT >20000 taka. 73% respondents were used smart phone. All respondents (100%) were used mobile phone for communicating with relatives & most of the cases (82.37%) reason was kill spare time. Frequently used social media sites was a Messenger (71.52%) followed by You Tube (68.13%) & Facebook (67.11%). 81.35% respondents were using mobile phones at home and 52.88% had no specific time for using a mobile phone. About 82.71% respondents were found monthly expenditure on mobile phone